2017
DOI: 10.1038/srep42461
|View full text |Cite
|
Sign up to set email alerts
|

Bio-functionalized magnetic nanoparticles for the immunoassay of fetal fibronectin: a feasibility study for the prediction of preterm birth

Abstract: Preterm birth is an important cause of perinatal morbidity and mortality. Various biomarkers in cervicovaginal secretions related to preterm birth have been investigated, of which foetal fibronectin (fFN) shows the greatest potential because of its high negative predictive value. The immunomagnetic reduction (IMR) assay has emerged as a novel quantitative method to detect biomarkers. In this prospective case-control study, we analysed 33 samples of cervicovaginal secretions from pregnant women between 22 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In our previous study, we demonstrated that detecting biomarkers in cervicovaginal secretions with an IMR assay had a lower LOD and better sensitivity and specificity compared with ELISA. 15 Third, we did not perform interference testing in this study. According to previous studies, no detectable interference effect was noted with the IMR assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that detecting biomarkers in cervicovaginal secretions with an IMR assay had a lower LOD and better sensitivity and specificity compared with ELISA. 15 Third, we did not perform interference testing in this study. According to previous studies, no detectable interference effect was noted with the IMR assay.…”
Section: Discussionmentioning
confidence: 99%
“…IMR assays have been shown to be able to detect biomarkers in body fluids with ideal specificity and sensitivity. [13][14][15][16] Few previous studies have evaluated the relationships between CRP or PCT in cervicovaginal secretions of pregnant women with PPROM and infection, and the results have been inconsistent. Furthermore, few studies have focused on early-onset neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Ramos-Gómez and coworkers demonstrated specific detection of Alzheimer's disease biomarkers using a nanoconjugate of IONPs and antiferritin antibodies at a nontoxic level [42]. In another work, Wong et al modified the surface of dextran-coated Fe 3 O 4 nanoparticles with antifetal fibronectin (fFN) antibody to detect the biomarker fFN for sensitive and accurate predictions of the risks of preterm birth [43].…”
Section: Integration Of Biomolecules and Magnetic Iron Oxide Nanopart...mentioning
confidence: 99%
“…The use of nanotechnology has been proposed for the treatment of preterm labor. This technology was suggested to improve the accuracy and cost-effectiveness of preterm delivery diagnosis by implementing a fibronectin test using magnetic nanoparticles coated with anti-fibronectin antibodies [ 91 ]. Furthermore, it was also applied to improve drug treatment.…”
Section: Preterm Birthmentioning
confidence: 99%